FPGA: targeted development system for embedded applications - Sklyarov, Valery (2013)
This paper considers approaches to the design and implementation of embedded systems using XC6200 FPGAs. The methods that are introduced enable the synthesis of circuits that are modifiable and extensible, and that provide a virtual function capability. The accepted behavioral specification supports modularity and hierarchy. The developed design tools allow translating this specification into dynamically modifiable control circuits. A method based on reconfigurable cores for rapid design of reconfigurable virtual datapath was suggested. A stand-alone board using one XC6216 FPGA was designed and two other solutions, currently under development, were discussed. They can be used as virtual embedded controllers. An integrated design environment (IDELS) has been developed to provide specification, synthesis, simulation, testing, debugging, and implementation of the circuits in hardware. The software has been developed using Visual C++ and allows access to both stand-alone and built-in PC boards.